2022
DOI: 10.3390/vehicles4040051
|View full text |Cite
|
Sign up to set email alerts
|

Real Time Predictive and Adaptive Hybrid Powertrain Control Development via Neuroevolution

Abstract: The real-time application of powertrain-based predictive energy management (PrEM) brings the prospect of additional energy savings for hybrid powertrains. Torque split optimal control methodologies have been a focus in the automotive industry and academia for many years. Their real-time application in modern vehicles is, however, still lagging behind. While conventional exact and non-exact optimal control techniques such as Dynamic Programming and Model Predictive Control have been demonstrated, they suffer fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…Therefore, this result shows that trying to find an equilibrium between the time at the intersection and acceleration-based energy consumption is unfeasible or at least leads to non-robust controllers-and that a two-level optimization would be required. This is compatible with the idea that local vehicle energy reduction can be achieved by using a local predictive energy management powertrain strategy that relies on the speed profile of the vehicle [17]-as opposed to an all-in-one solution purely relying on cohort speed control.…”
supporting
confidence: 56%
See 1 more Smart Citation
“…Therefore, this result shows that trying to find an equilibrium between the time at the intersection and acceleration-based energy consumption is unfeasible or at least leads to non-robust controllers-and that a two-level optimization would be required. This is compatible with the idea that local vehicle energy reduction can be achieved by using a local predictive energy management powertrain strategy that relies on the speed profile of the vehicle [17]-as opposed to an all-in-one solution purely relying on cohort speed control.…”
supporting
confidence: 56%
“…Indeed, mixing turning and non-turning operations inherently constrains the speed achievable for all vehicles and forces sub-optimal operation. These limitations prompted the authors to investigate the use of Artificial Intelligence, which demonstrated high energy savings with large heterogeneous cohorts operating at controlled intersection [16] and for local powertrain adaptive control [17]. Artificial intelligence offers a simple and fast development framework, low compute power requirements and high reusability thanks to its adaptiveness to a wide range of dynamics.…”
Section: Introductionmentioning
confidence: 99%